Production of Purified Sodium Chloride as Industrial Standard - Wiwit Sri Werdi Pratiwi; Makhfud Efendy; Nike Ika Nuzula; Mohammad Rahem; Fawait Afnani (Juvenil, 2023)
ABSTRACTThe research described about chemical treatments to increase percentage of sodium chloride from crude salt which was obtained from four districts on Madura Island. The conventional salt process contains percentage of sodium chloride 85.99%; 81.90%; 84.825% and 86.87% from Sumenep, Pamekasan, Sampang and Bangkalan respectively. Those results were still below the standard quality of industrial salt (98.5% of dry base). In this study, increasing percentage of sodium chloride was done by re-crystallization method. Crude salt was diluted with distilled water to form saturated solution, then added sodium hydroxide, barium chloride and hydrochloride acid to remove impurities such as magnesium hydroxide, calcium hydroxide, potassium hydroxide, barium sulfate, and carbonic acid. The results showed that the purified of sodium chloride enhanced 100.03%; 98.86%; 98.86% and 99.7% for salt products from Sumenep, Pamekasan, Sampang and Bangkalan, respectively and accepted by industrial standard.Keywords: Purified salt, chemical treatments, industrial standard